Calculated absorption and scattering properties of gold nanoparticles of different size, shape, and composition: Applications in biological imaging and biomedicine - Jain, PK; Lee, KS; El-Sayed, IH; El-Sayed, MA (AMER CHEMICAL SOC, 2006)
The selection of nanoparticles for achieving efficient contrast for biological and cell imaging applications, as well as for photothermal therapeutic applications, is based on the optical properties of the nanoparticles. We use Mie theory and discrete dipole approximation method to calculate absorption and scattering efficiencies and optical resonance wavelengths for three commonly used classes of nanoparticles: gold nanospheres, silica-gold nanoshells, and gold nanorods. The calculated spectra clearly reflect the well-known dependence of nanoparticle optical properties viz. the resonance wavelength, the extinction cross-section, and the ratio of scattering to absorption, on the nanoparticle dimensions. A systematic quantitative study of the various trends is presented. By increasing the size of gold nanospheres from 20 to 80 nm, the magnitude of extinction as well as the relative contribution of scattering to the extinction rapidly increases. Gold nanospheres in the size range commonly employed (similar to 40 nm) show an absorption cross-section 5 orders higher than conventional absorbing dyes, while the magnitude of light scattering by 80-nm gold nanospheres is 5 orders higher than the light emission from strongly fluorescing dyes. The variation in the plasmon wavelength maximum of nanospheres, i.e., from similar to 520 to 550 nm, is however too limited to be useful for in vivo applications. Gold nanoshells are found to have optical cross-sections comparable to and even higher than the nanospheres. Additionally, their optical resonances lie favorably in the near-infrared region. The resonance wavelength can be rapidly increased by either increasing the total nanoshell size or increasing the ratio of the core-to-shell radius. The total extinction of nanoshells shows a linear dependence on their total size, however, it is independent of the core/shell radius ratio. The relative scattering contribution to the extinction can be rapidly increased by increasing the nanoshell size or decreasing the ratio of the core/shell radius. Gold nanorods show optical cross-sections comparable to nanospheres and nanoshells, however, at much smaller effective size. Their optical resonance can be linearly tuned across the near-infrared region by changing either the effective size or the aspect ratio of the nanorods. The total extinction as well as the relative scattering contribution increases rapidly with the effective size, however, they are independent of the aspect ratio. To compare the effectiveness of nanoparticles of different sizes for real biomedical applications, size-normalized optical cross-sections or per micron coefficients are calculated. Gold nanorods show per micron absorption and scattering coefficients that are an order of magnitude higher than those for nanoshells and nanospheres. While nanorods with a higher aspect ratio along, with a smaller effective radius are the best photoabsorbing nanoparticles, the highest scattering contrast for imaging applications is obtained from nanorods of high aspect ratio with a larger effective radius.
Keywords: ENHANCED RAMAN-SCATTERING; SURFACE-PLASMON RESONANCE; OPTICAL-PROPERTIES; METAL NANOPARTICLES; ASPECT-RATIO; SILVER NANOPARTICLES; INDOCYANINE GREEN; REFRACTIVE-INDEX; LIGHT-SCATTERING; WAVE-GUIDES